SAT0379 Is Fatigue Immune-Mediated in Primary SjÖgren's Syndrome? Data from the Prospective Assess Cohort. (9th June 2015) - Gottenberg, J.E.; Seror, R.; Benessiano, J.; Devauchelle-Pensec, V.; Dieude, P.; Dubost, J.J.; Fauchais, A.L.; Goeb, V.; Hachulla, E.; Hatron, P.Y.; Larroche, C.; Le Guern, V.; et al.
Abstract : Background: Little is known about the pathogenesis of fatigue, a hallmark of primary Sjögren's syndrome. The respective contribution of depression, disease activity, or auto-immunity itself has never been studied ever since international disease activity scores were established. We therefore investigated the association between fatigue and other characteristics of the disease in a large multi-center prospective cohort. Methods: ASSESS is a multi-center prospective cohort which included 395 patients. At baseline and every year of the follow-up, systemic disease activity and patient-related outcome are evaluated by the ESSDAI and ESSPRI (the average of patient's visual analogic scales (VAS) for fatigue, pain and dryness), respectively, and patients fill questionnaires including the Hospital Anxiety and Depression (HAD) scale. Serum markers of B-cell activation, BAFF, interferon (IFN)-inducible chemokines, and IL-21 were assessed. Results: Median (25th-75th) fatigue VAS was 6 (4-8). Fatigue VAS was correlated with dryness VAS (r=0.46, p<0.0001) and pain VAS (r=0.54, p<0.0001). Fatigue VAS was not correlated with age or disease duration, the ESSDAI, unstimulated salivary flow or Schirmer's test. Fatigue VAS was significantly higher in patients with depression (defined by a HAD subscale for depression (HAD-D) ≥8 (median fatigue VAS of 7 (6-9) in patients with depression and of 6 (4-8) in patients without depression, p<0.0001). In patients without depression, fatigue VAS remained not associated with anti-SSA, the ESSDAI, unstimulated salivary flow and Schirmer's test. Among patients without depression, a high fatigue VAS (≥5, the median of fatigue VAS in these patients) was not associated with a higher level of serum IFN-inducible chemokines (CCL2, CXCL10, CCL19), B-cell activating cytokines such as BAFF or IL-21, markers of B-cell activation (total Ig levels, free light chains of immunoglobulins, rheumatoid factor levels). Conclusions: These results confirm the diversity of factors associated with fatigue in primary Sjögren's syndrome, including depression and the two other main symptoms, dryness and pain. Even when focusing on patients without depression, no association was observed between fatigue and systemic disease activity, autoantibody profile, serum surrogate markers of the IFN signature and of B-cell activation. Further work is necessary to determine the existence of potential other immunological drivers. Disclosure of Interest: None declared